4D Printing – Dawn of an Emerging Technology Cycle - Pei, Eujin (Assembly automation, 2014)
Purpose This article reviews state-of-the-art developments in 4D printing, discusses what it is, investigates new applications that have been discovered and suggests its future impact Design/methodology/approach The article clarifies the definition of 4D printing and describes notable examples covering material science, equipment and applications Findings This paper highlights an emerging technology cycle where 4D printing research has gained traction within additive manufacturing. The use of stimuli-responsive materials can be programmed and printed to enable pre-determined reactions when subject to external stimuli Originality/value This article reviews state-of-the-art developments in 4D printing, discusses what it is, investigates new applications that have been discovered and suggests its future impact